Outpacing the Commoditization of Your Brand - A Case Study of Citibank - Fallon, Pat; Senn, Fred (Marketing & Menedzsment, 2019)
The conventional wisdom is that people choose a bank based on purely rational criteria such as location and charges for ATM use and other services, and these assumptions lead to a “rates and fees” approach to marketing. When banks do attempt branding work, they typically operate on a narrow emotional bandwidth - friendly, neighborly, or trustworthy - but few have exhibited a genuine personality. Citibank hatched an audacious plan: to transform Citi into a global power brand, preeminent not only in financial services but also among other great consumer brands like Disney, Nike, or Coca-Cola. Even though they didn’t fully know what the term meant, they wanted to make Citi the world’s first “unbanklike” bank.